What the public think about participation in medical research during an influenza pandemic: an international cross-sectional survey. (December 2019) - Gobat, N.; Butler, C.C.; Mollison, J.; Francis, N.A.; Gal, M.; Harris, V.; Webb, S.A.R.; Byrne, J.-P.; Watkins, A.; Sukumar, P.; Hood, K.; Nichol, A.
Abstract: Objectives: The public and patients are primary contributors and beneficiaries of pandemic-relevant clinical research. However, their views on research participation during a pandemic have not been systematically studied. We aimed to understand public views regarding participation in clinical research during a hypothetical influenza pandemic. Study design: This is an international cross-sectional survey. Methods: We surveyed the views of nationally representative samples of people in Belgium, Poland, Spain, Ireland, the United Kingdom, Canada, Australia and New Zealand, using a scenario-based instrument during the 2017 regional influenza season. Descriptive and regression analyses were conducted. Results: Of the 6804 respondents, 5572 (81.8%) thought pandemic-relevant research was important, and 5089 (74.8%) thought 'special rules' should be applied to make this research feasible. The respondents indicated willingness to take part in lower risk (4715, 69.3%) and higher risk (3585, 52.7%) primary care and lower risk (4780, 70.3%) and higher risk (4113, 60.4%) intensive care unit (ICU) study scenarios. For primary care studies, most (3972, 58.4%) participants preferred standard enrolment procedures such as prospective written informed consent, but 2327 (34.2%) thought simplified procedures would be acceptable. For ICU studies, 2800 (41.2%) preferred deferred consent, and 2623 (38.6%) preferred prospective third-party consent. Greater knowledge about pandemics, trust in a health professional, trust in the government, therapeutic misconception and having had ICU experience as a patient or carer predicted increased willingness to participate in pandemic-relevant research. Conclusions: Our study indicates current public support for pandemic-relevant clinical research. Tailored information and initiatives to advance research literacy and maintain trust are required to support pandemic-relevant research participation and engagement. Highlights: There is strong public support for pandemic-relevant clinical research initiatives. Willingness to take part and to sign up under permissive approaches depends on type of research and key participant factors. Knowledge of pandemics, trust in doctors and government, and experience of critical illness influence research participation.